In vitro elution of amikacin and Dispersin B from a polymer hydrogel. Issue 5 (20th April 2020) - Hagen, Chris R. M.; Singh, Ameet; Weese, J. Scott; Marshall, Quinn; zur Linden, Alex; Gibson, Thomas W. G.
Abstract: Objective: To characterize the in vitro elution of amikacin and Dispersin B (β‐ N ‐acetylglucosaminidase) in a degradable hydrogel. Study design: In vitro, prospective study. Methods: Amikacin (group A; 40 mg/mL), Dispersin B (group D; 70 μg/mL), or combined amikacin and Dispersin B (group AD; 40 mg/mL and 70 μg/mL, respectively) were added to a hydrogel. Ten aliquots per group were incubated in phosphate‐buffered saline that was exchanged at 1, 4, 8, 12, and 24 hours and then once daily for 10 days. Eluted amikacin and Dispersin B were quantitated by using an amikacin reagent kit and a Dispersin B enzyme‐linked immunosorbent assay kit, respectively. Time point drug concentrations were compared between groups by using repeated‐measures analysis of variance, and total drug elution was compared by using an area under the curve calculation. Results: Amikacin alone, Dispersin B alone, and amikacin and Dispersin B combined together underwent rapid elution in the first 24 hours, followed by a gradual decrease over 10 days. The concentration of Dispersin B eluted in group D was higher at 1 day and lower from day 5 to day 10 compared with that in group AD. The concentration of amikacin eluted in group A was higher at 1, 4, and 8 hours and on day 10 and lower on day 1 compared with that in group AD. The total elution of amikacin was greater from group AD compared with that from group A ( P = .02). Conclusion: Combining amikacin and Dispersin B had an affect on the total elution of amikacin but not Dispersin B. Clinical significance: The combination of amikacin and Dispersin B in a degradable hydrogel could allow local treatment of complex infections without the requirement for multiple invasive procedures.